2011
DOI: 10.3844/ajabssp.2011.317.323
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability in <i>Rhizoctonia solani</i> Isolated from <i>Vitis vinifera</i> Based on Amplified Fragment Length Polymorphism

Abstract: Problem statement: Rhizoctonia solani is a potential grapevine pathogen. In order to develop effective methods of control, it is necessary to document its genetic diversity. Approach: The objective of this study was to analyze the genetic variability of R. solani isolated from the rhizosphere of ungrafted V. vinifera var. perlette seedless planted in Sonora, Mexico using Amplified Fragment Length Polymorphism (AFLP). Results: In the selective amplification using eight primer combinations we obtained a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…Therefore, AFLP markers combine the advantages of RFLP's and PCR-based markers. This technology has been adopted for fingerprinting and mapping of different plants (Hussein et al, 2005) as well as some pathogens (Meza-Moller et al, 2011). Omahinmin and Osawaru (2005) reported that high degree of wide morphological variation exist among accession of okra which requires further evidence using molecular markers to clarify.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AFLP markers combine the advantages of RFLP's and PCR-based markers. This technology has been adopted for fingerprinting and mapping of different plants (Hussein et al, 2005) as well as some pathogens (Meza-Moller et al, 2011). Omahinmin and Osawaru (2005) reported that high degree of wide morphological variation exist among accession of okra which requires further evidence using molecular markers to clarify.…”
Section: Discussionmentioning
confidence: 99%
“…AFLP analysis on 32 PT and 36 TB isolates placed them into two distinct groups based on their host. A similar genetic diversity study of R. solani AG4 isolates obtained from the rhizosphere of six vineyards in Mexico was reported by Meza-Moller et al [38]. They analysed 41 Rhizoctonia isolates using AFLP markers, which revealed three main groups in the UPGMA dendrogram and six groups from principal component analysis.…”
Section: Discussionmentioning
confidence: 75%
“…The complexity in homologous markers (alleles), representing this method less applicable for accurate research. Conversely the promptness and simplicity with reliability marks which could be created by AFLPs were making this method as a powerful molecular tool kit for ecologists and evolutionary biologists [65,66].…”
Section: Length Polymorphismsmentioning
confidence: 99%